2019
DOI: 10.1111/clr.13397
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peri‐implant disease and risk indicators in a Japanese population with at least 3 years in function—A multicentre retrospective study

Abstract: Objectives The aim of this study was to evaluate the prevalence of peri‐implant disease and analyze risk indicators in Japanese subjects with ≥3 years of implant function. Material and methods Five hundred and forty‐three subjects treated with 1,613 implants were evaluated. Information was collected about the patients’ physical and dental history, as well as implant details. Peri‐implant evaluation included probing depth, bleeding on probing (BoP), suppuration (Sup), and keratinized tissue width. Bone loss was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
49
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 47 publications
8
49
0
3
Order By: Relevance
“…On the other hand, Wada et al . reported a significant lower prevalence, with peri‐implant mucositis and peri‐implantitis being diagnosed at subject level in 23.9% and 15.8%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, Wada et al . reported a significant lower prevalence, with peri‐implant mucositis and peri‐implantitis being diagnosed at subject level in 23.9% and 15.8%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Another topic of debate is the role of smoking as a potential risk factor for peri‐implantitis. While several cross‐sectional studies reported a strong association between a current/history of smoking and peri‐implantitis (Degidi et al, ; Wada et al, ), other studies failed to confirm smoking as a relevant potential risk factor for peri‐implantitis (Marrone et al, ). This controversy is also illustrated by the conclusions reached by recent systematic reviews (Casado, Aguiar, Fernandes Pinheiro, Machodo, & Rosa Pinheiro, ; Schwarz, Derks, Monje, & Wang, ; Sgolastra, Petrucci, Severino, Gatto, & Monaco, ).…”
Section: Discussionmentioning
confidence: 99%
“…Irregular maintenance visits, poor oral hygiene and a history of periodontitis were found to increase the risk of peri‐implantitis (Derks et al, ; Roccuzzo, Bonino, Aglietta, & Dalmasso, ; Roos‐Jansåker, Lindahl, Renvert, & Renvert, ; Roos‐Jansåker, Renvert, Lindahl, & Renvert, ). Smoking (Degidi, Nardi, & Piattelli, ; Wada et al, ) and systemic diseases, such as diabetes (Daubert, Weinstein, Bordin, Leroux, & Flemmig, ) had been identified to be associated with a higher prevalence of peri‐implantitis. Some studies have reported a relationship between prosthetic factors and peri‐implantitis.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the factors that lead to peri-implant disease is crucial for maintaining the dental implants to function properly. Several patient-and implant-related risk indicators including poor oral hygiene, smoking, history of periodontal disease, and compliance of maintenance have been reported [2][3][4]7]. On the other hand, the necessity of keratinized tissue around implant is controversial.…”
mentioning
confidence: 99%